Preparation method of thiol-modified carboxymethyl starch hydrogel material and application thereof
Patent Information
- Application Number
- CN202310390848.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-04-13
AI Technical Summary
[0003]本发明解决的技术问题是提供了一种巯基改性羧甲基淀粉水凝胶材料的制备方法及其应用,针对淀粉分子链拉伸时易破裂、与导电纳米材料结合性能差且不具有智能性等缺点,使用巯基改性羧甲基淀粉分子链,以银纳米线、植酸与FeCl3·6H2O在水溶液中电离出的离子作为导电纳米材料,与聚乙烯醇、N-异丙基丙烯酰胺通过一锅法反应制备巯基改性羧甲基淀粉水凝胶材料,该方法制备的水凝胶材料具有优良的拉伸性能和较好的导电性能,且具有温度敏感性、自愈性和可回收利用性,能够用于制备温度/应变传感器
1、本发明选用的巯基改性羧甲基淀粉,能够均匀分布导电纳米材料银纳米线;
Smart Images

Figure CN116574273B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of preparation technology of multifunctional hydrogel materials, specifically relating to a method for preparing a thiol-modified carboxymethyl starch hydrogel material and its application. Background Technology
[0002] Hydrogels, as a novel flexible material, possess advantages such as high mechanical properties, good biocompatibility, and strong designability, and are expected to become a platform for next-generation wearable sensors. Starch, as one of the most abundant biopolymers, is one of the most promising materials for application in wearable sensors. Constructing hydrogel materials with high mechanical properties, good conductivity, and intelligence using starch as a raw material is of great significance for practicing my country's ecological civilization construction and promoting the development of sustainable, high-quality green manufacturing. However, starch molecular chains have drawbacks such as high rigidity and non-conductivity, resulting in hydrogels with poor mechanical properties and conductivity, limiting the development and application of starch-based hydrogel materials in the field of wearable sensors. Therefore, the development of starch-based hydrogel materials with good conductivity, functionality, and mechanical properties has attracted widespread attention. Patent document CN115160595A discloses a method for preparing a starch-based hydrogel that combines anti-swelling, anti-freezing, conductivity, and high tensile strength, which can be used in fields such as flexible wearable sensors, electronic skin, or tissue engineering. Patent document CN109354719A discloses a starch-based hydrogel with high tensile strength, high toughness, good shape plasticity, and self-healing properties, which can be used in fields such as biochemistry and biomedicine. However, the above-mentioned starch-based hydrogels still have the problem of low conductivity, and there is still a certain gap between them and practical applications. Summary of the Invention
[0003] The technical problem solved by this invention is to provide a method for preparing a thiol-modified carboxymethyl starch hydrogel material and its application. Addressing the shortcomings of starch molecular chains, such as easy breakage during stretching, poor bonding performance with conductive nanomaterials, and lack of intelligence, this invention uses thiol-modified carboxymethyl starch molecular chains, with ions ionized from silver nanowires, phytic acid, and FeCl3·6H2O in aqueous solution as conductive nanomaterials, and reacts them with polyvinyl alcohol and N-isopropylacrylamide in a one-pot reaction to prepare the thiol-modified carboxymethyl starch hydrogel material. The hydrogel material prepared by this method has excellent stretching properties and good conductivity, and also exhibits temperature sensitivity, self-healing, and recyclability, making it suitable for the fabrication of temperature / strain sensors.
[0004] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: a method for preparing a thiol-modified carboxymethyl starch hydrogel material, characterized in that the specific process is as follows: Step S1: Disperse carboxymethyl starch evenly in water at room temperature, then add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and stir to mix evenly to obtain material A; Step S2: Disperse L-cysteine evenly in material A at room temperature, then add hydrochloric acid solution to adjust the mixture to acidity, and stir to mix evenly to obtain material B; Step S3: Dialyze material B multiple times with hydrochloric acid solution under low temperature and light-proof environment to obtain material C; Step S4: Add FeCl3·6H2O to the phytic acid solution and heat and stir to mix evenly to obtain material D; Step S5: Add material C, N-isopropylacrylamide, 10wt% polyvinyl alcohol solution, 0.04g / mL sodium tetraborate solution and 0.0025g / mL silver nanowire solution to material D at 0~100℃ and stir to obtain material E; Step S6: Add potassium persulfate, the initiator, to material E at 90~100℃ and stir to obtain material F; Step S7: Place material F in a glass mold, cool to room temperature, then freeze at -24~0℃ for 8~12h and thaw. Repeat this process three times to finally obtain the target product, thiol-modified carboxymethyl starch hydrogel material.
[0005] The preparation method of the thiol-modified carboxymethyl starch hydrogel material of the present invention is characterized by the following specific steps: Step S1: Disperse 2g of carboxymethyl starch evenly in 200mL of water at room temperature, then add 50mM 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and stir at room temperature for 45min to obtain material A; Step S2: Disperse 0.5g of L-cysteine evenly in material A at room temperature, adjust the pH of the mixture to 4 using 1M hydrochloric acid solution, and stir for 3h to obtain material B; Step S3: Dialyze material B once with 5mM hydrochloric acid solution in a light-protected environment at 6℃, then dialyze twice with 5mM hydrochloric acid solution containing 1wt% NaCl, and finally dialyze twice with 1mM solution containing 1wt% NaCl to obtain material C. Step S4: Add 0.25g FeCl3·6H2O to 8mL of 50wt% phytic acid solution and heat and stir at 95℃ for 10~30min to obtain material D; Step S5: Add 1g of material C, 0.8g of N-isopropylacrylamide, 10mL of 10wt% polyvinyl alcohol solution, 2.5mL of 0.04g / mL sodium tetraborate solution and 2mL of 0.0025g / mL silver nanowire solution to material D at 95℃ and stir for 2h to obtain material E; Step S6: Add 0.02g of potassium persulfate initiator to material E at 95℃ and stir for 1h to obtain material F; Step S7: Place material F in a glass mold, cool to room temperature, freeze at -20℃ for 10 hours and then thaw. Repeat this process three times to finally obtain the target product, thiol-modified carboxymethyl starch hydrogel material.
[0006] The application of the thiol-modified carboxymethyl starch hydrogel material described in this invention in the preparation of flexible sensors.
[0007] In the preparation process of this invention, thiol groups (-SH) can interact with silver atoms in silver nanowires to form Ag-S bonds. Grafting -SH onto the carboxymethyl starch molecular chain as an intermediate layer between starch and silver nanowires effectively enhances the interfacial compatibility between the hydrophilic carboxymethyl starch and the hydrophobic silver nanowires, thereby improving the problem of uneven dispersion of silver nanowires in starch-based hydrogels. Furthermore, the introduction of polyvinyl alcohol (PVA) and carboxymethyl starch to construct a dynamic network structure through hydrogen bonding and borate ester bonds effectively improves the elongation at break and tensile strength of the starch-based hydrogel. The introduced phytic acid and Fe... 3+ It can form multiple hydrogen bonds and metal coordination with other components, enhancing the mechanical properties of starch-based hydrogels; and it introduces a large number of free ions, synergistically improving the conductivity of starch-based hydrogels with silver nanowires. Furthermore, since the hydrogel network is composed of dynamically reversible physical interactions and chemical bonds, the prepared hydrogels exhibit excellent recyclability and self-healing properties. Simultaneously, the addition of the temperature-responsive functional material N-isopropylacrylamide endows the hydrogel material with the functionality of rapidly responding to changes in ambient temperature, further broadening the application scope of hydrogel materials in the field of wearable sensors.
[0008] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The mercapto-modified carboxymethyl starch used in this invention can uniformly distribute conductive nanomaterials such as silver nanowires. 2. The N-isopropylacrylamide used in this invention is a widely used stimulus-responsive functional material, and the starch-based hydrogel prepared based on N-isopropylacrylamide has temperature sensitivity.
[0009] 3. The thiol-modified carboxymethyl starch hydrogel material prepared by this invention has excellent strain sensitivity. Attached Figure Description
[0010] Figure 1 The stress-strain curves of the target products G1-G3 prepared in Examples 1-3 under tension are shown. Figure 2The conductivity histograms for the target products G1-G3 prepared in Examples 1-3 are shown. Figure 3 Stress-strain curves of the target product G1 prepared in Example 1 after self-healing for different times; Figure 4 Stress-strain curves of the target product G1 prepared in Example 1 before and after 5 recycling cycles; Figure 5 The compressive stress-strain curve of the target product G1 prepared in Example 1 under 10 cycles; Figure 6 A graph showing the relative resistance of the target product G1 prepared in Example 1 as a function of temperature. Figure 7 The graph shows the relative resistance of the target product G1 prepared in Example 1 as a function of wrist bending. Detailed Implementation
[0011] The following examples further illustrate the above-described content of the present invention, but it should not be construed as limiting the scope of the subject matter of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention. Example
[0012] Step S1: Disperse 2g of carboxymethyl starch evenly in 200mL of water at room temperature, then add 50mM 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and stir at room temperature for 45min to obtain material A; Step S2: Disperse 0.5g of L-cysteine evenly in material A at room temperature, adjust the pH of the mixture to 4 using 1M hydrochloric acid solution, and stir for 3h to obtain material B; Step S3: Dialyze material B once with 5mM hydrochloric acid solution in a light-protected environment at 6℃, then dialyze twice with 5mM hydrochloric acid solution containing 1wt% NaCl, and finally dialyze twice with 1mM hydrochloric acid solution containing 1wt% NaCl to obtain material C. Step S4: Add 0.25g FeCl3·6H2O to 8mL of 50wt% phytic acid solution and heat and stir at 95℃ for 20min to obtain material D; Step S5: Add 1g of material C, 0.8g of N-isopropylacrylamide, 10mL of 10wt% polyvinyl alcohol solution, 2.5mL of 0.04g / mL sodium tetraborate solution and 2mL of 0.0025g / mL silver nanowire solution to material D at 95℃ and stir for 2h to obtain material E; Step S6: Add 0.02g of potassium persulfate initiator to material E at 95℃ and stir for 1h to obtain material F; Step S7: Place material F in a glass mold, cool to room temperature, freeze at -20℃ for 10 hours and then thaw. Repeat this process three times to obtain the target product G1. Example
[0013] Step S1: Disperse 2g of carboxymethyl starch evenly in 200mL of water at room temperature, then add 50mM 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and stir at room temperature for 45min to obtain material A; Step S2: Disperse 0.5g of L-cysteine evenly in material A at room temperature, adjust the pH of the mixture to 4 using 1M hydrochloric acid solution, and stir for 3h to obtain material B; Step S3: Dialyze material B once with 5mM hydrochloric acid solution in a light-protected environment at 6℃, then dialyze twice with 5mM hydrochloric acid solution containing 1wt% NaCl, and finally dialyze twice with 1mM hydrochloric acid solution containing 1wt% NaCl to obtain material C. Step S4: Add 0.25g FeCl3·6H2O to 10mL of 50wt% phytic acid solution and heat and stir at 95℃ for 10min to obtain material D; Step S5: Add 1g of material C, 0.8g of N-isopropylacrylamide, 10mL of 10wt% polyvinyl alcohol solution, 2.5mL of 0.04g / mL sodium tetraborate solution and 2mL of 0.0025g / mL silver nanowire solution to material D at 95℃ and stir for 2h to obtain material E; Step S6: Add 0.02g of potassium persulfate initiator to material E at 95℃ and stir for 1h to obtain material F; Step S7: Place material F in a glass mold, cool to room temperature, freeze at -24℃ for 10 hours and then thaw. Repeat this process three times to obtain the target product G2. Example
[0014] Step S1: Disperse 2g of carboxymethyl starch evenly in 200mL of water at room temperature, then add 50mM 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and stir at room temperature for 45min to obtain material A; Step S2: Disperse 0.5g of L-cysteine evenly in material A at room temperature, adjust the pH of the mixture to 4 using 1M hydrochloric acid solution, and stir for 3h to obtain material B; Step S3: Dialyze material B once with 5mM hydrochloric acid solution in a light-protected environment at 6℃, then dialyze twice with 5mM hydrochloric acid solution containing 1wt% NaCl, and finally dialyze twice with 1mM hydrochloric acid solution containing 1wt% NaCl to obtain material C. Step S4: Add 0.25g FeCl3·6H2O to 12mL of 50wt% phytic acid solution and heat and stir at 95℃ for 30min to obtain material D; Step S5: Add 1g of material C, 0.8g of N-isopropylacrylamide, 10mL of 10wt% polyvinyl alcohol solution, 2.5mL of 0.04g / mL sodium tetraborate solution and 2mL of 0.0025g / mL silver nanowire solution to material D at 95℃ and stir for 2h to obtain material E; Step S6: Add 0.02g of potassium persulfate initiator to material E at 95℃ and stir for 1h to obtain material F; Step S7: Place material F in a glass mold, cool to room temperature, freeze at 0°C for 10 hours and then thaw. Repeat this process three times to obtain the target product G3.
[0015] The target product G1 was cut to a size of 15mm × 5mm. A tensile test was performed on the target product using a universal testing machine, ensuring the sample retained a 5mm length after clamping. Target products G2 and G3 were tested using the same method. Electrochemical impedance spectroscopy (EIS) was performed using an electrochemical workstation. A piece of hydrogel measuring 10mm (length) × 5mm (width) × 2.5mm (thickness) was sandwiched between two copper sheets. The voltage frequency range was 1Hz-1MHz, and the bias voltage was 10mV. Connecting wires to both ends of the conductive hydrogels prepared in the above embodiments yields a wearable sensor. The hydrogel was then used to monitor data related to changes in body temperature and movement using the electrochemical workstation. The performance of the samples in all embodiments is as follows: Figure 1 The figure shows the tensile curves of the target products G1, G2, and G3 obtained in Examples 1-3, with tensile strengths of 137 kPa, 76 kPa, and 30 kPa, respectively. Figure 2 As shown, the conductivity of the target products G1, G2, and G3 obtained in Examples 1-3 is 23.6 S / m, 27.7 S / m, and 33.7 S / m, respectively. Figure 3 As shown, the stress-strain curves of the target product G1 obtained in Example 1 after self-healing for different times are displayed. The test results show that the hydrogel material has excellent self-healing properties. Figure 4 As shown, the stress-strain curves of the target product G1 obtained in Example 1 before and after 5 recycling cycles are presented. The test results show that the hydrogel material still has excellent mechanical properties after 5 recycling cycles. Figure 5 As shown, the compressive stress-strain curve of the target product G1 obtained in Example 1 under 10 cycles is presented. The test results indicate that the hydrogel material has excellent energy dissipation capability. Figure 6As shown, the target product G1 obtained in Example 1 was used to fabricate a temperature sensor. By changing the temperature of the heat source back and forth between 25°C and 60°C, the sensor's response electrical signal was recorded. The test results show that the flexible sensor fabricated based on the target product has good responsiveness to temperature changes. Figure 7 As shown, the target product G1 obtained in Example 1 was used to prepare a strain sensor and attached to the human wrist. The response signal of the sensor was recorded when the wrist was repeatedly bent. The test results showed that the flexible sensor prepared based on the target product had good responsiveness to strain.
[0016] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are only illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from the scope of the principles of the present invention, and all such changes and modifications fall within the protection scope of the present invention.
Claims
1. A method for preparing a mercapto-modified carboxymethyl starch hydrogel material, characterized in that... The specific process is as follows: Step S1: Disperse carboxymethyl starch evenly in water at room temperature, then add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and stir to mix evenly to obtain material A; Step S2: Disperse L-cysteine evenly in material A at room temperature, then add hydrochloric acid solution to adjust the mixture to acidity, and stir to mix evenly to obtain material B; Step S3: Dialyze material B multiple times with hydrochloric acid solution under low temperature and light-proof environment to obtain material C; Step S4: Add FeCl3·6H2O to the phytic acid solution and heat and stir to mix evenly to obtain material D; Step S5: Add material C, N-isopropylacrylamide, 10wt% polyvinyl alcohol solution, 0.04g / mL sodium tetraborate solution and 0.0025g / mL silver nanowire solution to material D at 0~100℃ and stir to obtain material E; Step S6: Add potassium persulfate, the initiator, to material E at 90~100℃ and stir to obtain material F; Step S7: Place material F in a glass mold, cool to room temperature, then freeze at -24~0℃ for 8~12h and thaw. Repeat this process three times to finally obtain the target product, thiol-modified carboxymethyl starch hydrogel material.
2. The method for preparing the thiol-modified carboxymethyl starch hydrogel material according to claim 1, characterized in that... The specific steps are as follows: Step S1: Disperse 2g of carboxymethyl starch evenly in 200mL of water at room temperature, then add 50mM 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and stir at room temperature for 45min to obtain material A; Step S2: Disperse 0.5g of L-cysteine evenly in material A at room temperature, adjust the pH of the mixture to 4 using 1M hydrochloric acid solution, and stir for 3h to obtain material B; Step S3: Dialyze material B once with 5mM hydrochloric acid solution in a light-protected environment at 6℃, then dialyze twice with 5mM hydrochloric acid solution containing 1wt% NaCl, and finally dialyze twice with 1mM hydrochloric acid solution containing 1wt% NaCl to obtain material C. Step S4: Add 0.25g FeCl3·6H2O to 8mL of 50wt% phytic acid solution and heat and stir at 95℃ for 10~30min to obtain material D; Step S5: Add 1g of material C, 0.8g of N-isopropylacrylamide, 10mL of 10wt% polyvinyl alcohol solution, 2.5mL of 0.04g / mL sodium tetraborate solution and 2mL of 0.0025g / mL silver nanowire solution to material D at 95℃ and stir for 2h to obtain material E; Step S6: Add 0.02g of potassium persulfate initiator to material E at 95℃ and stir for 1h to obtain material F; Step S7: Place material F in a glass mold, cool to room temperature, freeze at -20℃ for 10 hours and then thaw. Repeat this process three times to finally obtain the target product, thiol-modified carboxymethyl starch hydrogel material.
3. The application of the thiol-modified carboxymethyl starch hydrogel material prepared by the method according to any one of claims 1 to 2 in the preparation of flexible sensors.
Citation Information
Patent Citations
Starch double-crosslinking network hydrogel and preparation method thereof
CN109354719A
Anti-freezing and anti-swelling starch-based nano composite hydrogel as well as preparation method and application thereof
CN115160595A
Hydrogel, preparation method thereof, and application of hydrogel in preparation of sensing chip
CN110947344A
Preparation method and application of green flexible conductive anti-freezing hydrogel
CN112521630A